Penanggulangan Kejahatan Pidana Politik Dalam Undang-Undang Pemilihan Umum (Pemilu) - Endri Endri (Jurnal Selat, 2014)
Politics of crime prevention in general election law are interesting to be discuss because some prohibited acts already set out, for example, there are minimum specific criminal provisions and additional punishment for it perpetrators. Thus seemed to guarantee the implementation of a good election, yet in fact there are a variety of criminal acts which qualified as offense, criminal elections, etc. The offenses contained in the various election rules such as the Criminal Code, legislative elections laws and presidential election law are a criminal offense related to the general election. In other words, this criminal act also called as part of political criminal or political crimes. The legislative products which mentioned any punishments in the election laws means of political crime prevention offenses (criminal offense and elections). However it’s necessary implemented for the general elections and suitable with the principles of direct, general, free, confidential, and fair. Keywords: Crime Prevention, Political Crime And Elections